A COMPARISON OF ULTRASOUND-GUIDED SUPRACLAVICULAR VERSUS INFRACLAVICULAR BLOCKS FOR HAND AND FOREARM SURGERIES - ANANYA HAGJER; DEEPANNITA SUTRADHAR; RUPANKAR NATH; SUNEETA DUTTA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Regional anesthesia, particularly techniques such as supraclavicular (SCB) and infraclavicular (ICB) blocks, is increasingly favored over general anesthesia for upper limb surgeries due to its safety and efficacy, especially with ultrasound guidance. Methods: A study was conducted at Silchar Medical College and Hospital involving 120 patients undergoing elective hand and forearm surgeries. These patients were randomly divided into SCB and ICB groups. Each block was performed using ultrasound guidance with an 8-MHz ultrasonic linear scanning probe. Patients received pre-medication, including pantoprazole/ranitidine, ondansetron, and midazolam (anxiolytic dose), 15 min before the procedure. The aim of our study was to compare the efficacy of ultrasound guidance in SCB block versus ICB block in terms of sensory and motor block, time taken to visualize structures, block performance time, and observe other parameters such as complications. Results: Significant differences were observed between the SCB and ICB groups in terms of systolic BP, diastolic BP, and mean arterial pressure (MAP). The SCB group exhibited a higher MAP, whereas the ICB group required more time for structure visualization and block performance. However, the ICB group achieved complete sensory blocks quicker than the SCB group. Needle advancements were more frequent in the SCB group as compared to the ICB group. Conclusion: The study concluded that while the ICB group had a longer block performance time, it experienced fewer complications, making ultrasound-guided ICB block a more effective option for upper limb surgeries compared to the SCB block.